Cyclic fatigue and torsional strength of three different thermally treated reciprocating nickel-titanium instruments (vol 22, pg 1879, 2018) - Alcalde, Murilo Priori; Hungaro Duarte, Marco Antonio; Bramante, Clovis Monteiro; Vasconselos, Bruno Carvalho de; Tanomaru-Filho, Mario [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Pinto, Jader Camilo [UNESP]; Reis So, Marcus Vinicius; Vivan, Rodrigo Ricci (Springer, 2018)
The original version of this article contained a mistake. The name Jader Carvalho Pinto should have been Jader Camilo Pinto.